Developing Teachers’ Soft Skills within the New Educational Paradigm: Competences, Values, Indicators, Results - Sydorenko, Viktoriia V.; Dzhus, Oksana; Kozenko, Roman V.; Ivanenko, Olena A.; Zavadska, Tetiana M. (Acta Paedagogica Vilnensia, 2022)
This paper deals with theoretical models of soft skills development in teacher education. The immediate purpose of this consideration is to develop a model for the development of a teacher’s soft skills as a competent, innovative, motivated, and competitive specialist in the labor market in the present time. The role of soft skills in the process of professional development of employees in all organizations has been increasing in recent times. However, the importance and necessity of teachers’ soft skills and, therefore, their formation among students studying in pedagogical areas are not yet adequately realized by many participants in the educational process. This paper examines the concept of soft skills and identifies the importance of these skills for the development of a specialist in the pedagogical field. In addition, a comparative analysis of hard skills and soft skills was conducted, and their components, namely competences, values, and behavioral indicators were evaluated. An analysis was conducted to assess the labor market needs for new qualifications. This made it possible to design a model of the modern teacher with skills reflective of their real environment. The results of this study can be further used in the improvement of lifelong learning and adult education.
Keywords: educational paradigm; competence; skill; ongoing professional training; social skills; social harmony